2013
DOI: 10.1002/jcu.22030
|View full text |Cite
|
Sign up to set email alerts
|

Isolated torsion of the fallopian tube with hydrosalpinx mimicking a multiloculated ovarian cyst: Whirlpool sign on preoperative sonography and MRI

Abstract: Isolated torsion of the fallopian tube is a rare case of lower abdominal pain. Early diagnosis of such cases is crucial because it allows for the possibility of salvage surgery and the prevention of irreversible vascular damage. However, diagnosis is rarely made before surgery due to nonspecific clinical and imaging features. We report a case of isolated tubal torsion with specific imaging findings on preoperative ultrasonography, color Doppler ultrasonography, and magnetic resonance imaging that was misdiagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…While MRI whirlpool sign has been described for ovarian torsion in Indian literature, this is probably the first description of MRI whirlpool sign being employed (in the Indian subcontinent) for diagnosis of tubal torsion. 14,15 This case reinforces the fact that in presence of whirlpool sign with normal appearing ovaries, there is a high index of radiological suspicion for tubal torsion which by itself is a rare entity.…”
Section: Case Reportsupporting
confidence: 69%
“…While MRI whirlpool sign has been described for ovarian torsion in Indian literature, this is probably the first description of MRI whirlpool sign being employed (in the Indian subcontinent) for diagnosis of tubal torsion. 14,15 This case reinforces the fact that in presence of whirlpool sign with normal appearing ovaries, there is a high index of radiological suspicion for tubal torsion which by itself is a rare entity.…”
Section: Case Reportsupporting
confidence: 69%
“…If USG is indeterminate, Contrast-enhanced MRI may be useful, to identify (1) the twisted vascular pedicle, (2) uterine deviation to the twisted side (3) thickened and enhanced Fallopian tube, (4) also particularly useful in young adolescents or pregnant women without ionizing radiation. [ 10 ] Color Doppler may be useful in diagnosing the IFTT, but normal flow definitely will not rule out the torsion. A whirlpool sign is known for its high sensitivity in diagnosing the IFTT,[ 9 11 ] which was not assessed in our study; hence, the diagnosis could be missed and none of the patients were identified as adnexal torsion by imaging modality in our series.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is reported to be much more useful for making this distinction; however, MRI is not always performed in an emergency scenario. 10 …”
Section: Discussionmentioning
confidence: 99%